A Study on the Impact of Social Trust on Farmers’ Agricultural Waste Resource Utilization Behavior in the Context of Environmental Regulation Policy - Jianhua Wang; Ling Ma (Agriculture)
The resource utilization of agricultural waste is an important way to achieve the green transformation of agriculture. Based on micro-survey data from 701 farmers in Jiangsu Province, this paper constructs a binary logistic model to explore how farmers’ social trust affects their decisions regarding agricultural waste resource utilization. It also examines the moderating effect of environmental regulation policies between the two. The results show that social trust has a significant positive impact on farmers’ agricultural waste resource utilization behavior. Secondly, guiding environmental regulation policies positively moderate the effect of interpersonal trust on farmers’ agricultural waste resource utilization behavior, while both guiding and restrictive environmental regulation policies serve as substitute moderators in the relationship between institutional trust and farmers’ participation behavior. Finally, heterogeneity analysis shows that, due to differences in household endowments, the impact of interpersonal trust and institutional trust on agricultural waste resource utilization behavior differs across different farmer groups. Therefore, this paper suggests cultivating and enhancing the level of social trust among farmers, thereby promoting their participation in waste resource utilization while strengthening the regulatory role of environmental regulation policies in shaping farmers’ behavior.